Effect of acyclovir therapy on the outcome of mechanically ventilated patients with lower respiratory tract infection and detection of herpes simplex virus in bronchoalveolar lavage: protocol for a multicentre, randomised controlled trial (HerpMV) - Hagel, Stefan; Brillinger, Nicole; Decker, Sebastian; Deja, Maria; Ertmer, Christian; Fiedler, Sandra; Franken, Philipp; Heim, Markus; Weigand, Markus A.; Zarbock, Alexander; Pletz, Mathias (BMJ open, 2024)
Introduction Herpes simplex virus (HSV) is frequently detected in the respiratory tract of mechanically ventilated patients and is associated with a worse outcome. The aim of this study is to determine whether antiviral therapy in HSV-positive patients improves outcome. - Methods and analysis Prospective, multicentre, open-label, randomised, controlled trial in parallel-group design. Adult, mechanically ventilated patients with pneumonia and HSV type 1 detected in bronchoalveolar lavage (≥105 copies/mL) are eligible for participation and will be randomly allocated (1:1) to receive acyclovir (10 mg/kg body weight every 8 hours) for 10 days (or until discharge from the intensive care unit if earlier) or no intervention (control group). The primary outcome is mortality measured at day 30 after randomisation (primary endpoint) and will be analysed with Cox mixed-effects model. Secondary endpoints include ventilator-free and vasopressor-free days up to day 30. A total of 710 patients will be included in the trial. - Ethics and dissemination The trial was approved by the responsible ethics committee and by Germany’s Federal Institute for Drugs and Medical Devices. The clinical trial application was submitted under the new Clinical Trials Regulation through CTIS (The Clinical Trials Information System). In this process, only one ethics committee, whose name is unknown to the applicant, and Germany’s Federal Institute for Drugs and Medical Devices are involved throughout the entire approval process. Results will be published in a journal indexed in MEDLINE and CTIS. With publication, de-identified, individual participant data will be made available to researchers. - Trial registration number NCT06134492.